Triady homograficzne w języku rosyjskim - Kaliszan, Jerzy (Studia Rossica Posnaniensia, 2016)
The article is devoted to the study of Russian homographic rows consisting of three components, such as ворона (gen. and acc. sg. of ворон ‘raven’) — ворона (nom. sg.) ‘crow’ — ворона (short form of вороной ‘black’), вертела (gen. sg. of вертел ‘spit for roasting’) — вертела (nom. and acc. pl. of вертел) — вертела (past of вертеть ‘to turn’), здорово (adv.) ‘greatly, superbly; hard, strongly’ — здорово (short neut. form of здоровый I ‘healthy’) — здорово (short neut. form of здоровый II ‘tremendous, hefty’). The author has analyzed and classified 70 such three-component groups of homographs revealed in contemporary Russian.